Parvovirus B19 Immunity among Iranian patients with Human Immunodeficiency Virus (HIV) infection - alireza abdollahi; saeed shoar; nasrin shoar (Mediterranean Journal of Hematology and Infectious Diseases)
Human Parvovirus B19 (PVB19) is among the etiology of aplastic crisis in HIV infected patients. Although studies have indicated the importance of such an infection among immunocopromised patients, seroprevalence of this infection differs worldwide.